# Solve for w 0=11- square root of 12+11w

0=11-12+11w
Rewrite the equation as 11-12+11w=0.
11-12+11w=0
Subtract 11 from both sides of the equation.
-12+11w=-11
Multiply each term in -12+11w=-11 by -1
Multiply each term in -12+11w=-11 by -1.
(-12+11w)⋅-1=(-11)⋅-1
Multiply -12+11w⋅-1.
Multiply -1 by -1.
112+11w=(-11)⋅-1
Multiply 12+11w by 1.
12+11w=(-11)⋅-1
12+11w=(-11)⋅-1
Multiply -11 by -1.
12+11w=11
12+11w=11
To remove the radical on the left side of the equation, square both sides of the equation.
12+11w2=112
Simplify each side of the equation.
Multiply the exponents in ((12+11w)12)2.
Apply the power rule and multiply exponents, (am)n=amn.
(12+11w)12⋅2=112
Cancel the common factor of 2.
Cancel the common factor.
(12+11w)12⋅2=112
Rewrite the expression.
(12+11w)1=112
(12+11w)1=112
(12+11w)1=112
Simplify.
12+11w=112
Raise 11 to the power of 2.
12+11w=121
12+11w=121
Solve for w.
Move all terms not containing w to the right side of the equation.
Subtract 12 from both sides of the equation.
11w=121-12
Subtract 12 from 121.
11w=109
11w=109
Divide each term by 11 and simplify.
Divide each term in 11w=109 by 11.
11w11=10911
Cancel the common factor of 11.
Cancel the common factor.
11w11=10911
Divide w by 1.
w=10911
w=10911
w=10911
w=10911
The result can be shown in multiple forms.
Exact Form:
w=10911
Decimal Form:
w=9.90‾
Mixed Number Form:
w=91011
Solve for w 0=11- square root of 12+11w

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top